PENGARUH SENAM AEROBIC LOW IMPACT DAN RELAKSASI NAFAS DALAM TERHADAP KADAR GULA DARAH PADA LANSIA PENDERITA DIABETES MELLITUS DI POSYANDU ANGGREK KARTASURA - Ari Murti Septiani; Atiek Murharyati; Dewi Suryandari (Journal of Advanced Nursing and Health Sciences, 2020)
Diabetes Mellitus (DM) is a carbohydrate, protein, and fat metabolism disorder marked with hyperglycemia or blood glucose increase due to an abnormality of insulin secretion or decreased work performance of insulin. One of the handlers of Diabetes Mellitus is exercise. Low impact aerobic gymnastics is a gymnastics with low to moderate intensities, easy-to-do movements, injury-free movements, rhythmic movements, non-jerking movements, and rare sudden movement. Breathing relaxation is a breathing exercise which consists of abdomen breathing and purse lip breathing to reduce stress. The objective of this research is to investigate the effect of low impact aerobic gymnastics and deep breathing relaxation on blood sugar level of the diabetes mellitus elderly at Anggrek Integrated Health Post of Kartasura. This research uses quantitative method with a quasi-experimental research design with a pre-test and post-test approach without control group design. The result of the Wilcoxon’s Test shows that the p-value was 0.000 which was less than 0.05, meaning that the administration of low impact aerobic gymnastics and deep breathing relaxation could reduce the blood sugar level of the diabetes mellitus elderly. Thus, the low impact aerobic gymnastics and deep breathing relaxation had an effect on the blood sugar level of the diabetes mellitus elderly at Anggrek Integrated Health Post of Kartasura.